Severe Leptospirosis (Weil's Disease) with Multiple Organ Failure in Urban Setting: A Case Report - Halim, Samuel; Hartono, Bryan Arista (Institute of Topical Disease Universitas Airlangga, 2023)
Leptospirosis is a rare disease that could cause multiple organ failures and death if left untreated. The correct treatment will determine the recovery of patients. A 28-years old male came to the Emergency Department with profuse diarrhea. No prior medical history; worked as a private employee recently assigned to collect rat traps one week before. Laboratories show severe thrombocytopenia, acute liver failure, and acute renal failure support by imaging with the conclusion of hepatomegaly with normal kidney size. During observation in the emergency room, the patient worsens into septic shock. The patient was treated in intensive care, diagnosed with Weil's disease, and treated given antibiotics with aggressive fluid therapy; dialysis was postponed, and close monitoring of the patient's symptoms and organ function. After five days of care, clinical symptoms and organ function improved, and the patient was discharged well. Diagnosis of Leptospirosis is challenging with a combination of signs and symptoms that are not commonly found. Therefore, primary treatment is antibiotic and supportive care such as renal replacement therapy is not routinely needed as long there are improvements in close monitoring. This objective is to increase awareness and treatment option for further severe leptospirosis cases